Malignant lymphoma of the cervix uteri: histology and ultrastructure. Issue 8 (August 1976) - Carr, I; Hill, A S; Hancock, B; Neal, F F
Abstract : Two cases of primary lymphoma of the cervix uteri are described. Both responded to radiotherapy; both were composed at the ultrastructural level of mature macrophages and immature, apparently neoplastic lymphoreticular cells and are classified as reticulum cell lymphoma.